Nitrogen content identification in crop plants using spectral reflectance and artificial neural networks - Covolan Ulson, J. A. [UNESP]; Benez, S. H. [UNESP]; Nunes Da Silva, I. [UNESP]; Nunes De Souza, A. [UNESP] (My University, 2001)
The accurate identification of the nitrogen content in crop plants is extremely important since it involves economic aspects and environmental impacts. Several experimental tests have been carried out to obtain characteristics and parameters associated with the health of plants and its growing. The nitrogen content identification involves a lot of nonlinear parameters and complexes mathematical models. This paper describes a novel approach for identification of nitrogen content thought spectral reflectance of plant leaves using artificial neural networks. The network acts as identifier of relationships among pH of soil, fertilizer treatment, spectral reflectance and nitrogen content in the plants. So, nitrogen content can be estimated and generalized from an input parameter set. This approach can be form the basis for development of an accurate real time nitrogen applicator.